Facile conversion of water to functional molecules and cross-linked polymeric films with efficient clusteroluminescence - Bo Song; Jianyu Zhang; Jiadong Zhou; Anjun Qin; Jacky W. Y. Lam; Ben Zhong Tang (Nature Communications, 2023)
Abstract Exploring approaches to utilize abundant water to synthesize functional molecules and polymers with efficient clusteroluminescence properties is highly significant but has yet to be reported. Herein, a chemistry of water and alkyne is developed. The synthesized products are proven as nonaromatic clusteroluminogens that could emit visible light. Their emission colors and luminescent efficiency could be adjusted by manipulating through-space interaction using different starting materials. Besides, the free-standing polymeric films with much high photoluminescence quantum yields (up to 45.7%) are in situ generated via a water-involved interfacial polymerization. The interfacial polymerization-enhanced emission of the polymeric films is observed, where the emission red-shifts and efficiency increases when the polymerization time is prolonged. The synthesized polymeric film is also verified as a Janus film. It exhibits a vapor-triggered reversible mechanical response which could be applied as a smart actuator. Thus, this work develops a method to synthesize clusteroluminogens using water, builds a clear structure-property relationship of clusteroluminogens, and provides a strategy to in situ construct functional water-based polymeric films.